Association between extracted copper and dissolved organic matter in dairy-manure amended soils. (March 2019) - Araújo, Eloá; Strawn, Daniel G.; Morra, Matthew; Moore, Amber; Ferracciú Alleoni, Luis Reynaldo
Abstract: Dairy manure often has elevated concentrations of copper (Cu) that when applied to soil may create toxicity risks to seedlings and soil microbes. Manure application also increases dissolved organic matter (DOM) in soil solution. We hypothesize that high rates of dairy manure amendment over several years will cause increased DOM in the soil that complexes Cu, increasing its mobility. To test this hypothesis, this study investigated water soluble Cu concentrations and dissolved organic carbon (DOC) in soil samples from 3 years of manure-amended soils. Samples were collected at two depths over the first 3 years of a long-term manure-amendment field trial. DOC, Cu, Fe, and P concentrations were measured in water extracts from the samples. Ultraviolet/visible (UV/Vis) spectra were used to assess the DOC characteristics. After 3 years of manure application, extractable Cu concentration was approximately four times greater in the surface and two times greater in subsurface samples of manure-amended soils as compared to non-amended control soils and traditional mineral fertilizer-amended soils. The extractable Cu concentration was greatest in plots that had the highest manure amendment rates (35 t ha −1 and 52 t ha −1, dry weight). The UV/Vis parameters SUVA254 and E2 /E3 correlated with Cu concentration in the extracts (p < 0.05), suggesting that DOC characteristics are important in Cu-binding. The molecular characteristics of the DOC in the subsurface after 3 years of manure amendment were distinct from the DOC in the control plot, suggesting that manure amendment creates mobile DOC that may facilitate Cu mobilization through soil. The 10-fold increase in extractable Cu concentration after only 3 years of manure application indicates that repeated applications of the dairy manure sources used in this study at rates of 35 t/ha or greater may create risks for Cu toxicity and leaching of Cu into ground and surface waters. Graphical abstract: Image 1 Highlights: Application of dairy manure to alkaline soil increases soil Cu concentration. Dissolved organic matter in soil from manure application facilitates Cu mobility. Water extraction of manure-amended soils showed correlations between dissolved organic carbon, Cu, Fe, and P. UV/Vis and FTIR spectral analysis suggest that DOM characteristics are important in Cu-binding to DOM. Abstract : Application of dairy manure to alkaline soil increases soil DOC and Cu concentration. Dissolved organic matter in soil from manure application facilitates Cu mobility.